2005
DOI: 10.2298/jsc0501125o
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling and simulation of gel drying with supercritical carbon dioxide

Abstract: Mathematical models of alumina/silica gel supercritical drying with carbon dioxide were studied using supercritical drying experimental data. An alumina/silica gel with zinc chloride was synthesized and dried with superciritical carbon dioxide, and its weight change was monitored as a function of drying time. The pore size distribution of the obtained aerogel was determined using the BET method and nitrogen adsorption/ desorption. The mathematical model of the supercritical drying of the wet gel was represente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Eqs. (10) and (12) show that the convective mass flux of ethanol at the alcogel surface is equal to diffusive mass flux of ethanol at the interface between the alcogel and the flowing stream.…”
Section: Modeling Of Drying Of Cylindrical Silica Alcogelmentioning
confidence: 99%
See 1 more Smart Citation
“…Eqs. (10) and (12) show that the convective mass flux of ethanol at the alcogel surface is equal to diffusive mass flux of ethanol at the interface between the alcogel and the flowing stream.…”
Section: Modeling Of Drying Of Cylindrical Silica Alcogelmentioning
confidence: 99%
“…Orlović et al [12] investigated supercritical drying of alumina/silica alcogel with carbon dioxide in a 70 cm 3 tubular extractor (Autoclave Engineers Supercritical Extraction Screening System) at 313 K and 80 bar. The pores of the gel were entirely filled with of 1-butanol (solvent).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure In some studies, the tortuosity value was reported to be in the range of (1-6) including the calculated tortuosity value for this study [23][24][25][26] .…”
Section: Page 19 Of 25mentioning
confidence: 90%
“…As an example of 1D mass transfer models, the study of Orlovic et al, on the drying of alumina/silica alcogel the pores of which were filled with 1-butanol can be given [86]. The developed model was represented as an unsteady one-dimensional diffusion of solvent through pores of the gel.…”
Section: Kinetics Of Supercritical Dryingmentioning
confidence: 99%
“…However, the findings of the study of Orlovic et al indicated that increasing the temperature affected the drying time considerably. As elevated temperatures led to an increased solubility of the solvent used (1-butanol), drying times were significantly reduced [86]. It was shown that changing operating conditions such as temperature and pressure affected the diffusion coefficient which thereby affected the drying time.…”
Section: Kinetics Of Supercritical Dryingmentioning
confidence: 99%